2022
DOI: 10.3389/fpubh.2022.970751
|View full text |Cite
|
Sign up to set email alerts
|

Trends of myopia development among primary and junior school students in the post-COVID-19 epidemic period

Abstract: PurposeTo investigate the trends of myopia among primary and junior school students in the post-COVID-19 epidemic period.MethodA prospective of cross-sectional study using spot photoscreenings in 123,538 children among primary and junior school students from 2019 to 2021 was conducted to evaluate the development of myopia in Xuzhou, China in the post-COVID-19 epidemic period. Equivalent refraction and the prevalence of myopia were recorded.ResultsThe spherical equivalent refraction of myopia decreased across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Another study that investigated the trends of myopia among primary and junior school students in the post-COVID-19 epidemic period over 3 years also reported the changes in the prevalence of different myopia degrees. 31 From the data, it can be observed that the trend of increasing prevalence of moderate to high myopia started from the 4th grade, which is consistent with the ndings of our study. Nonetheless, our study, which investigated the changes over a solitary semester, yielded the same outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Another study that investigated the trends of myopia among primary and junior school students in the post-COVID-19 epidemic period over 3 years also reported the changes in the prevalence of different myopia degrees. 31 From the data, it can be observed that the trend of increasing prevalence of moderate to high myopia started from the 4th grade, which is consistent with the ndings of our study. Nonetheless, our study, which investigated the changes over a solitary semester, yielded the same outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also demonstrated that education was a risk factor for myopia through diverse methods 14,25–27 . Meanwhile, our latest research confirmed that myopia rates in graduating for the primary or junior grades increased during the post–COVID-19 epidemic period 28 . Therefore, lighter learning tasks for preschool children have less impact on the myopia rate.…”
Section: Discussionsupporting
confidence: 60%
“…14,[25][26][27] Meanwhile, our latest research confirmed that myopia rates in graduating for the primary or junior grades increased during the post-COVID-19 epidemic period. 28 Therefore, lighter learning tasks for preschool children have less impact on the myopia rate. In addition, school-aged children were at increased risk of myopia following the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike us, Zhou et al found that the SE level of female students was consistently lower than that of male students from 2019 to 2022, and SE decreased with grade for primary and junior school students. 8 This seems to suggest that if we do not take action, the overall visual condition of girls will worsen, despite finding that non-myopic girls had higher SE levels than non-myopic boys in subgroup analysis. As for BMI, Theophanous et al 16 did not find any impact on myopia, 17 but two studies targeting young men found an association between BMI and myopia.…”
Section: Discussionmentioning
confidence: 97%
“…As per Zhou et al , myopia rates among primary school students in grades 2–4 increased during COVID-19 pandemic, with rates of 19.1%, 33.0% and 49.5% in 2021, respectively. 8 …”
Section: Introductionmentioning
confidence: 99%